2008
DOI: 10.1007/s00392-008-0728-8
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of plasma NT-pro-BNP levels in patients with atrial fibrillation and preserved left ventricular ejection fraction

Abstract: Plasma NT-pro-BNP levels were significantly higher in patients with paroxysmal and permanent AF compared to those with sinus rhythm in the setting of preserved left ventricular systolic function. LVEF and LAD were independent predictors of NT-pro-BNP levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 22 publications
3
35
0
1
Order By: Relevance
“…All of the above results indicate that serum Gal-3 levels were higher in persistent AF patients than in SR controls, and intracardiac Gal-3 can be used as a potential fibrosis biomarker in atrial samples. Besides, plasma NT-proBNP levels were significantly higher in patients with paroxysmal and persistent AF compared to those with SR in the setting of preserved left ventricular systolic function [36]; thus, we also tested serum NTproBNP levels, and the results also validated our previous conclusions that PeAF patients have higher coronary sinus serum NT-proBNP levels than SR controls.…”
Section: Discussionsupporting
confidence: 68%
“…All of the above results indicate that serum Gal-3 levels were higher in persistent AF patients than in SR controls, and intracardiac Gal-3 can be used as a potential fibrosis biomarker in atrial samples. Besides, plasma NT-proBNP levels were significantly higher in patients with paroxysmal and persistent AF compared to those with SR in the setting of preserved left ventricular systolic function [36]; thus, we also tested serum NTproBNP levels, and the results also validated our previous conclusions that PeAF patients have higher coronary sinus serum NT-proBNP levels than SR controls.…”
Section: Discussionsupporting
confidence: 68%
“…Demographic, clinical, and laboratory features that are well known to be related to the interplay between ischemic stroke and AF are more commonly observed in patients with nonsustained AF with respect to patients with normal findings on Holter monitoring, but are still not as common as those observed in longer durations of AF. [25][26][27] All these findings fit well into the recent observations that short supraventricular runs designate initial stages of left atrial remodeling and therefore are a predictor of future AF. 12,13 Leaving aside the prognostic value in predicting conversion into persistent AF, the more critical question is whether nonsustained AF plays a similar role in stroke pathophysiology like its persistent or paroxysmal equivalents.…”
supporting
confidence: 83%
“…В настоящем исследовании, в которое не толь-ко включили самое большое число пациентов с крат-кой продолжительностью ФП (определение по дан-ным литературы), но и проанализировали их данные отдельно пациентов с более длительными эпизода-ми ФП, предположили, что объединение пациентов с короткими и длительными эпизодами ФП не может быть полностью обосновано. Демографические, кли-нические и лабораторные особенности, которые, как известно, связаны с наличием как ИИ, так и ФП, чаще наблюдали у пациентов с неустойчивой ФП по сравнению с пациентами с нормальными результата-ми холтеровского мониторирования, но не так часто, как у пациентов с более длительными эпизодами ФП [25][26][27]. Все эти данные хорошо вписываются в последние наблю-дения, согласно которым наличие коротких суправен-трикулярных пробежек указывает на начальные стадии ремоделирования левого предсердия, в связи с чем явля-ется предиктором развития ФП в будущем [12,13].…”
Section: ■ обсуждениеunclassified
“…Hwang et al [12] showed that the measurement of NT-pro-BNP added incremental predictive value to LA size and diastolic function before AF ablation. In patients with preserved left ventricular systolic function, AF and LA sizes have been shown to be independent predictors of NT-pro-BNP [10,20]. In our study, the baseline values of NT-pro-BNP and LA size Fig.…”
Section: Nt-pro-bnpmentioning
confidence: 70%
“…AF also causes changes in the endocrine functions of the atria, and AF patients have higher levels of natriuretic peptides [9][10][11]. Plasma N-terminal pro-B-type natriuretic peptide (NT-pro-BNP) correlates with left atrial (LA) size [12] and epidemiological studies have identified it as a predictor of the development of AF [13].…”
Section: Introductionmentioning
confidence: 99%